Employers' perceptions of breastfeeding practice of employed mothers in Addis Ababa, Ethiopia: a qualitative study - Firmaye Bogale Wolde; Jemal Haidar; Yalemwork Getnet (BMC, 2022)
Abstract Background The Ethiopian Demographic and Health Survey 2019 shows that 59% of children are exclusively breastfed for the first 6 months of life, then the rate decreases sharply with age. Nearly half of the Ethiopian labor force (46%) is comprised of women. This is encouraging since women's employment is one way of ensuring women's empowerment. However, various factors related to employment make it one of the commonly mentioned factors contributing for the low prevalence of breastfeeding. Hence, there needs to be a conducive work environment that accommodates maternal needs to not fall back from empowerment and to improve breastfeeding practice. There are not many studies in Ethiopia that focus on work environment in relation with employers' experience and their perception of breastfeeding of employed mothers. Therefore, this study aims to explore employers' experience and perception of employed mothers' breastfeeding experience in different working environments in Addis Ababa, Ethiopia. Methods A qualitative study design using a descriptive phenomenology strategy was employed in this study and purposive sampling technique was used to recruit study participants. Data was collected between December 2016 and May 2017 in Addis Ababa city from 10 employers from private, governmental and non-governmental institutions through an in-depth interview. Thematic data analysis was performed where collected data was organized, coded and categorized into themes to give meaningful contributions to answering the research questions. Results Understanding breastfeeding, current maternity leave, perception of breastfeeding supporting the conditions and mother-friendly work environment were the themes generated after analysis. Almost all employers in this study recognized the importance of breastfeeding despite their different work environments and they also acknowledged the importance of making the working environment mother-friendly for stability and motivation of employed mothers. Conclusions Providing mothers with a friendly environment is understood as a positive thing by employers. The current maternity leave of 3 months has low acceptance and both onsite childcare center and six-month maternity leave are believed to help in creating a mother-friendly work environment despite their pros and cons.